Women in Newar Cultural Practices of Bhaktapur Municipality: Representation, Empowerment and Change - Phelu, Rajan (Bagiswori Journal, 2025)
This paper aims to explore the representation of women in the Newar cultural practices for their socio-economic change in Bhaktapur Municipality. Gender ideology is created in a society and manifested in various ways. Among several approaches, cultural practices are crucial in establishing and expressing gendered culture in the society at large. This paper examines women’s position in traditional Newar cultural practices through the perspective of gender performativity, challenging the notion that there is a single, universal experience of womanhood that applies to all women regardless of their culture, class, and race. Gender performativity refers to the concept that gender is socially constructed and continuously performed through repeated actions, behaviors, and expressions, rather than anything innate or biologically determined. Bhaktapur Municipality is widely recognized for its festivals, traditional dances, art, culture, and Newari way of life. The major deities of the two major religions, Buddhism and Hinduism, are thought to have contributed to the evolution of the enigmatic, vibrant, and thrilling ancient festivals that are still observed today. Throughout the year, numerous festivals are observed to commemorate historical and legendary events, to honor the gods, and to mark the shift of the seasons. This qualitative study analyzes how women are portrayed in cultural traditions of Bhaktapur Municipality by applying narrative research design. Primary data were collected through in-depth, semi-structured interviews and field-based observation whereas secondary data were gathered from books, journals and online databases. The finding of the article suggests that despite all the barriers of patriarchal power, Newar women have an influential position in indigenous cultural practices. Along with the significant participation in the cultural practices, the Newar women have learnt the indigenous skills and knowledge which are applied to produce the local products. Many Newar women have turned into entrepreneurs by following the local skills in the production of the goods. The growing number of female entrepreneurs is a highly effective way of promoting women's socioeconomic development, gender equality, and women's empowerment.